2019
DOI: 10.24095/hpcdp.39.5.02
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer risk by occupation in the Occupational Disease Surveillance System (ODSS) in Ontario, Canada

Abstract: Introduction Previous Canadian epidemiologic studies have identified associations between occupations and prostate cancer risk, though evidence is limited. However, there are no well-established preventable risk factors for prostate cancer, which warrants the need for further investigation into occupational factors to strengthen existing evidence. This study uses occupation and prostate cancer information from a large surveillance cohort in Ontario that linked workers’ compensation claim data to admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 42 publications
4
17
3
Order By: Relevance
“…We found a positive association with PCa risk for Production Supervisors and General Foremen as observed in two North American case-control studies [16,17]. Some negative associations have also been observed in our study with Service Workers with conflicting results in the literature [5,13,16] and with Food and Beverage Processers, Blacksmiths, Toolmakers and Machine-Tool Operators, Material-Handling and Related Equipment Operators, Dockers and Freight Handlers as observed in other original studies [5][6][7][8]12].…”
Section: Discussionsupporting
confidence: 85%
“…We found a positive association with PCa risk for Production Supervisors and General Foremen as observed in two North American case-control studies [16,17]. Some negative associations have also been observed in our study with Service Workers with conflicting results in the literature [5,13,16] and with Food and Beverage Processers, Blacksmiths, Toolmakers and Machine-Tool Operators, Material-Handling and Related Equipment Operators, Dockers and Freight Handlers as observed in other original studies [5][6][7][8]12].…”
Section: Discussionsupporting
confidence: 85%
“…The nding contradicts the study of the Ghana prostate study, which found a high association of prostate cancer amongst men in formal occupation [48]. The study agrees to studies that have associated informal work such as farming, construction as posing a high risk to prostate cancer [49,50]. Even though we did not isolate speci c occupation and its association with prostate cancer, we can infer that since most of the general population in the study setting are into farming and strenuous activitybased work, physical activity may play a role.…”
Section: Resultscontrasting
confidence: 63%
“…We cannot rule out the role of unmeasured confounding for those risk factors unavailable in this study but known to be associated with the reported cancers (eg, family history of cancer, ultraviolet radiation from the sun, diet) or residual confounding because of imperfectly measured risk factors (eg, pack-years smoking) in the reported estimates. Similarly, a large proportion of our study sample comprises firefighters, police, and construction workers, and increased cancer incidence among these occupation-specific groups has been previously reported ( 8 , 31 , 32 , 55 ). Occupational details (eg, years of service) were unavailable in this study, making it difficult to rule out the role of occupation in reported estimates ( 28 , 56 ).…”
Section: Discussionsupporting
confidence: 53%